2000
DOI: 10.1111/j.1365-2621.2000.tb15998.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Functional Properties of Rice Bran Proteins Modified by Commercial Exoproteases and Endoproteases

Abstract: Large portions of rice bran protein cannot be solubilized by mild solvents, but endoprotease use increases protein recovery. Bran was treated with 2 commercial proteases to achieve 8% to 9% peptide bond hydrolysis. The exo-plus endprotease was preferred to just using endopeptidases as it allowed the production of protein hydrolysates with enhanced functional properties. Solubility and emulsification activity and stability of hydrolysates produced with the protease blends were greater than that produced with en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 13 publications
7
92
0
1
Order By: Relevance
“…Contrariwise, this addition of a greater quantity of Flavourzyme would lead to higher DH, which is not sought after. Indeed, during hydrolysis, Alcalase, which is an endo-peptidase, leads to peptides [26], whereas Flavourzyme leads to peptides by its endo-peptidase activity and to amino acids by its exo-peptidase activity [26,31]. The aim of this work is to produce peptides with a mean length of 3-4 amino acids (DH & 30%).…”
Section: Resultsmentioning
confidence: 99%
“…Contrariwise, this addition of a greater quantity of Flavourzyme would lead to higher DH, which is not sought after. Indeed, during hydrolysis, Alcalase, which is an endo-peptidase, leads to peptides [26], whereas Flavourzyme leads to peptides by its endo-peptidase activity and to amino acids by its exo-peptidase activity [26,31]. The aim of this work is to produce peptides with a mean length of 3-4 amino acids (DH & 30%).…”
Section: Resultsmentioning
confidence: 99%
“…Protein has been extracted from rice bran for various food and pharmaceutical applications [2][3][4][5][6] . Rice bran protein has been used as hypoallergenic milk replacers in infant formulas 4) .…”
Section: Introductionmentioning
confidence: 99%
“…By using a-amylase, protein extraction could be promoted by hydrolyzing a-1,4-glycosidic linkage to release starch bound proteins 7 . Tang et al 18 , also reported a potent ability of a-amylase to recover proteins from plant cellular matrix 13 . Considering Viscozyme-L, it is a cocktail enzyme consisting of arabinase, cellulase, β-glucosidase, hemicellulase, and xylanase, so it might effectively enhance protein liberation from the matrix 7,18 .…”
Section: Preparation and Characterization Of Rice Bran Proteinmentioning
confidence: 99%
“…15 and 1 , respectively. The protein content in defatted rice bran was reported to be 12-20 7 and 15.4 13 .…”
Section: Preparation and Characterization Of Rice Bran Proteinmentioning
confidence: 99%
See 1 more Smart Citation